A New Concept Linking Observable Stable Isotope Fractionation to Transformation Pathways of Organic Pollutants - Elsner, Martin; Zwank, Luc; Hunkeler, Daniel; Schwarzenbach, René P. (My University, 2005)
Measuring stable isotope fractionation of carbon, hydrogen, and other elements by Compound Specific Isotope Analysis (CSIA) is a new, innovative approach to assess organic pollutant degradation in the environment. Central to this concept is the Rayleigh equation which relates degradation-induced decreases in concentrations directly to concomitant changes in bulk (= average over the whole compound) isotope ratios. The extent of in situ transformation may therefore be inferred from measured isotope ratios in field samples, provided that an appropriate enrichment factor (εbulk) is known. This εbulk value, however, is usually only valid for a specific compound and for specific degradation conditions. Therefore, a direct comparison of εbulk values for different compounds and for different types of reactions has in general not been feasible. In addition, it is often uncertain how robust and reproducible εbulk values are and how confidently they can be used to quantify contaminant degradation in the field. To improve this situation and to achieve a more in-depth understanding, this critical review aims to relate fundamental insight about kinetic isotope effects (KIE) found in the physico(bio)chemical literature to apparent kinetic isotope effects (AKIE) derived from εbulk values reported in environmentally oriented studies. Starting from basic rate laws, a quite general derivation of the Rayleigh equation is given, resulting in a novel set of simple equations that take into account the effects of (1) nonreacting positions and (2) intramolecular competition and that lead to position-specific AKIE values rather than bulk enrichment factors. Reevaluation of existing εbulk literature values result in consistent ranges of AKIE values that generally are in good agreement with previously published data in the (bio)chemical literature and are typical of certain degradation reactions (subscripts C and H indicate values for carbon and hydrogen):  AKIEC = 1.01−1.03 and AKIEH = 2−23 for oxidation of C−H bonds; AKIEC = 1.03−1.07 for SN2-reactions; AKIEC = 1.02−1.03 for reductive cleavage of C−Cl bonds; AKIEC = 1.00−1.01 for C=C bond epoxidation; AKIEC = 1.02−1.03 for C=C bond oxidation by permanganate. Hence, the evaluation scheme presented bridges a gap between basic and environmental (bio)chemistry and provides insight into factors that control the magnitude of bulk isotope fractionation factors. It also serves as a basis to identify degradation pathways using isotope data. It is shown how such an analysis may be even possible in complex field situations and/or in cases where AKIE values are smaller than intrinsic KIE values, provided that isotope fractionation is measured for two elements simultaneously (“two-dimensional isotope analysis”). Finally, the procedure is used (1) to point out the possibility of estimating approximate εbulk values for new compounds and (2) to discuss the moderate, but non-negligible variability that may quite generally be associated with εbulk values. Future research is suggested to better understand and take into account the various factors that may cause such variability.